Computer studies of the operation of a Three Phase Four Wire Shunt Active Power Filter applied to the Industry - Nova, Bruno Pereira (2022)
EAI SESC 2021 - 3rd EAI International Conference on Sustainable Energy for Smart Cities (online event), November 24 – 26, 2021 - Portugal.